Characterisation and modelling of static recovery process of plain stainless steel - Mohd Aizad, Kamarol (2008)
Annealing is a process where a material undergoes heat treatment for an extended time period and then slowly cooled. This process is very useful to alter the structure of the material where the grain size of the material tested change. The mechanical properties such as ductility and toughness also change during the annealing process. In this research, the recovery stage which is one of the annealing processes is being investigated. The material that has been use is type 304 stainless steel. At the recovery temperature which is in the range of 100oC-400 oC, the behavior of stainless steel being investigated and the degree of softening, Xrec is calculated using Friedel’s model. Friedel’s model is a mathematical model used to calculate the degree of softening. There are 36 specimens being tested and from this experiment, 3 graphs plotted which are Xrec vs Time, Xrec vs Temperature and Xrec vs Pre-strain. Using Friedel’s model, the activation energy, Q is calculated and being compared with other journal. The Q value obtained from Xrec vs Time and Xrec vs Temperature graphs are 466kJ/mol and 154kJ/mol respectively. There is no comparison made with Xrec vs Pre-strain graph. The Q value obtained from the graph plotted and from the journal is almost the same. So, the Friedel’s model is valid to calculate the degree of softening at static recovery temperature of stainless steel. From this whole research, the behavior of stainless steel at static recovery temperature can be predicted using the model. This is very useful to apply at the real life problem such as buildings and structure that using stainless steel as material.